Associated Risk Factors of Insomnia among Elderly People in Banepa Municipality - Pradhan, Rubi; Shrestha, Sumina; Lakhe, Dibyashwori; Kayastha, Babita; Sainju, Sapana (Janaki Medical College Journal of Medical Science, 2023)
Background & Objective: Insomnia is defined as a difficulty with the initiation, maintenance, duration, or quality of sleep that results in the impairment of daytime functioning. The prevalence of insomnia increases steadily with age and is often a persistent problem, particularly in older adults and is often mistaken as a normal part of ageing. The objective was to identify the associated risk factors of insomnia among elderly. Material and Methods: A descriptive cross-sectional research design was adopted. The data was collected from respondents in 60 samples using probability systematic random sampling technique. Data was collected using standard questionnaire tool i.e. Pittsburgh Insomnia Rating Scale 20 version. Descriptive statistics (frequency and percentage) and inferential statistics (Chi-square) were applied using Statistical Package for Social Science (SPSS) Version 16 for data analysis. Results: Study finding revealed that the mean age of the respondents was 77.5. Half of respondents i.e. (50.0%) had insomnia. There is significant association between insomnia and drinking alcohol (p=0.045), fear of death (p=0.032) and alter sleep due to bad dreams (p=0.035) and there is no significant association between insomnia and co-morbidity (p>0.05). Conclusion: It was concluded that 50% of the respondents had insomnia. Drinking alcohol, fear of death and alter sleep due to bad dreams are significant association with insomnia. Therefore, it would be better if awareness programs regarding stress management and lifestyle modification are given to the patient to improve the quality of life.